Update on blood‐based biomarkers for chronic liver diseases prognosis: Literature review and institutional experience. Issue 11 (30th October 2021) - Iwasa, Motoh; Shigefuku, Ryuta; Eguchi, Akiko; Tamai, Yasuyuki; Takei, Yoshiyuki
Abstract: Liver cirrhosis is the final stage of chronic liver disease (CLD) and is associated with high morbidity and mortality. Various complications such as portal hypertension, ascites retention, hepatic encephalopathy, and hepatorenal syndrome deeply affect patient outcome. The most common tools to predict the outcome of a CLD patient include the following: assessing severity of portal hypertension; scoring systems such as the model of end‐stage liver disease and Child–Pugh score and blood biomarkers related to complications and/or survival rate. In this article, we summarize recent studies of noninvasive markers for predicting impending complications related to CLD and discuss the clinical value of currently available blood biomarkers based on evidence from the literature. In addition, noninvasive blood biomarker assays for different prognostic functions were validated on 113 liver cirrhosis patients at our institution using Kaplan–Meier curve analysis to confirm that these markers can satisfactorily predict CLD‐related patient death. Abstract : The possibility of quantifying biomarkers for the prediction of chronic liver diseases with complication. Biomarkers indicate the condition of complication and some biomarkers can be used for the prediction of survival.